Promoting business process management excellence in Russia: Proceedings and report of the PropelleR 2012 Workshop held in Moscow, April 24 to 26, 2012 - Jörg Becker; Martin Matzner (Westfälische Wilhelms-Universität Münster, European Research Center for Information Systems (ERCIS), 2013)
BPM research has been of great importance in Germany since the early 1990s. In Russia, increased competition and new IT possibilities have only recently forced both companies and governmental institutions to start taking benefits from BPM. Against this background, the workshop PropelleR 2012 brought together German and Russian BPM researchers as well as practitioners in order to discuss recent BPM trends and challenges. The guiding question addressed by PropelleR 2012 was: 'How can the growing complexity of business processes in German-Russian relations be addressed by a holistic BPM approach?' This report includes a set of articles that reflect the PropelleR workshop participants' viewpoints on this question.
Keywords: 650; Business Process Management; PropelleR; Russia; German-Russian Year of Science 2011/2012